2006
DOI: 10.4067/s0718-19572006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characterization of the silverside fish Odontesthes regia (Humboldt, 1833) (Teleostei: Atheriniformes: Atherinopsidae) from Iquique, Chile

Abstract: Abstract.-This paper describes the karyotype ofOdontesthes regia by means of Giemsa staining, C-banding, to reveal the distribution of the constitutive heterochromatin, and by Ag-staining and fluorescent in situ hybridization (FISH), to locate ribosomal genes (rDNA). The chromosome diploid modal count in the species was 2n = 48. The karyotype is composed of one submetacentric pair (pair 1), 16 subtelocentric pairs (pairs 2 to 17), and 7 acrocentric pairs (pairs 18 to 24). With the exception of pair 1 it was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They comprise important fisheries resources and also present great ecological importance as forage species. Cytogenetic studies revealed a conserved diploid number of 48 chromosomes and the absence of morphologically distinguishable sex chromosomes in three in Odontesthes species [10,19,20]. This study investigated whether the amhy gene is conserved in 10 species of the Odontesthes genus from both the Pacific and Atlantic coasts, as well as some inland habitats, since information on genotypic sex determination of atherinopsids is limited to O. hatcheri and O. bonariensis .…”
Section: Introductionmentioning
confidence: 99%
“…They comprise important fisheries resources and also present great ecological importance as forage species. Cytogenetic studies revealed a conserved diploid number of 48 chromosomes and the absence of morphologically distinguishable sex chromosomes in three in Odontesthes species [10,19,20]. This study investigated whether the amhy gene is conserved in 10 species of the Odontesthes genus from both the Pacific and Atlantic coasts, as well as some inland habitats, since information on genotypic sex determination of atherinopsids is limited to O. hatcheri and O. bonariensis .…”
Section: Introductionmentioning
confidence: 99%